APLIKASI SISTEM KALKULASI PRODUKSI TELUR AYAM PETELUR DESA PAKUJATI BERBASIS ANDROID - SUNARYONO SUNARYONO; SULISTIYASNI SULISTIYASNI; DEWI ERLA MAHMUDAH; AMINRULLOH BIJAK BESTARI (LPPM STMIK Widya Utama, 2023)
Abstract — Calculation of chicken egg production is the process of calculating chicken eggs. In this calculation there is a comparison of the number of eggs produced in a given time period. Calculation of egg production can use Android as an information medium. Therefore, the researchers conducted a study entitled Chicken Egg Production Production System in Pakujati Village Based on Android. The purpose of this study is to help laying hens in calculating egg production.In this paper an application is made that can display information through android. The method used is RUP (Rational Unifield Process). The application used is Android Studio.The results of the benefit test conducted once by 20 testers showed the highest value in the Learnability aspects (easy to learn) and Efficiency aspects (efficient).The Android-based Pakujati Chicken Egg Production Calculation System has been tested for its performance using Valid's overall value Black Box Testing and can provide information or learning about the calculation of chicken egg production in Pakujati village. Keywords: Android, Calculations, Eggs, Rational Unifield Process, Android Studio